Принципи побудови паралельних обчислювальних систем - Адамович, В. Р. (ХНУРЕ, 2020)
The main types of parallel computers are considered, the differences are classified according to the level at which the hardware supports parallelism: multicore, multiprocessor – computers that have many computing elements within a single machine, as well as clusters, MPP, and grid systems that use many computers to work on a single task. Specialized parallel architectures are sometimes used alongside traditional processors to speed up specific tasks.
Keywords: паралельні обчислення; багатоядерний процесор; симетричний мультипроцесор; кластер